Moving forward in uncertainty? A serious game for validating interventions in public–private collaboration for sustainable mobility - Ruben Akse; Simone Ritter; Wijnand Veeneman; Vincent Marchau (Transportation Research Interdisciplinary Perspectives)
Public and private actors who realize mobility innovations in practice often aim to reduce uncertainty through traditional project management strategies. These approaches define an end goal and use predictive tools to explore scenarios and risks. It is thereby assumed that more research is necessary and agreement can be found among decision-makers. In practice, however, these conditions are rarely met in innovation processes. Alternative strategies to deal with uncertainty have been proposed in literature that are more focused on relations between decision-makers and exploring possibilities in an iterative way, such as shared visioning and other collaborative approaches. The question is how to stimulate actors to use these approaches in practice. This study tested how altering actor perspectives and views about uncertainty led to more collaborative responses to uncertainty. A comparison has been made in a serious game setting between a baseline control session, where uncertainty was negatively framed and rewarded, and an intervention session, where uncertainty was positively framed and rewarded. The game simulated a multi-actor decision-making process of negotiating about mobility innovations for a sustainable mobility plan. We found that in both sessions, actors used collaborative strategies to deal with uncertainty, but in the control session, participants were also applying control strategies for their own organization to reduce uncertainty because of the inhibiting conditions on mindset and synergy. The results of this study indicate that bringing decision-makers in a more positive arrangement toward uncertainty leads to better multi-actor collaboration, driving sustainable mobility innovations forward.